2021
DOI: 10.1177/03000605211029808
|View full text |Cite
|
Sign up to set email alerts
|

Factors predicting technical difficulties during endoscopic submucosal excavation for gastric submucosal tumor

Abstract: Objective Endoscopic submucosal excavation (ESE) has been established as an effective method for removal of gastric submucosal tumors (SMTs). The aim of the present study was to explore risk factors for technical difficulties in ESE. Methods In this retrospective study, we collected clinical data from patients who underwent ESE for gastric SMTs. Difficult ESE was defined as a procedure time ≥90 minutes, piecemeal resection, and/or occurrence of major adverse events. Univariate and multivariate analyses were pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 28 publications
1
10
0
Order By: Relevance
“…The ESE procedure ( Figure 2 ) and EFTR procedure ( Figure 3 ) were performed as previously reported. 20–22
Figure 2 ESE treatment of solitary gastric neurofibroma. ( A ) Submucosal bulge of posterior gastric fundus; ( B ) EUS showed that the solitary GN was hypoechoic; ( C ) incision and stripping of tumor mucosa; ( D ) exposing and excavating lesions; ( E ) ESE wound after tumor excavation; ( F ) metal clip to close the wound; ( G ) excavated tumor specimen.
…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The ESE procedure ( Figure 2 ) and EFTR procedure ( Figure 3 ) were performed as previously reported. 20–22
Figure 2 ESE treatment of solitary gastric neurofibroma. ( A ) Submucosal bulge of posterior gastric fundus; ( B ) EUS showed that the solitary GN was hypoechoic; ( C ) incision and stripping of tumor mucosa; ( D ) exposing and excavating lesions; ( E ) ESE wound after tumor excavation; ( F ) metal clip to close the wound; ( G ) excavated tumor specimen.
…”
Section: Methodsmentioning
confidence: 99%
“…The postoperative management was performed as previously reported. 20–22 Patients were fasted for 3–5 days and gradually transitioned to a normal diet in two weeks, all of whom intravenous proton-pump inhibitor (PPI) and antibiotics were used for 3 days. Patients need to review gastroscopy at the 3th, 6th, 12th months after the ESE/EFTR for the first year, and then once a year.…”
Section: Methodsmentioning
confidence: 99%
“…A limitation with ESD is risk of perforation for submucosal mass lesions arising from the muscularis propria layer due to the depth of the involvement. Both STER and ESE are minimally invasive techniques with high reported complete resection rates [5 ▪▪ ,30 ▪ ]. The STER technique involves creation of a submucosal tunnel via a longitudinal incision typically performed 5 cm proximal to the lesion followed by resection and retrieval of the lesion and then closure of the tunnel via endoscopic clips or suture.…”
Section: Management: Emerging Endoscopic Therapeutic Modalitiesmentioning
confidence: 99%
“…Procedural difficulty in EFTR may be variable depending on endoscopist experience, 39 lesion size, 40 and tumor location. Submucosal tumors in the fundus have been associated with greater technical difficulty during endoscopic resection 41,42 .…”
Section: Endoscopic Resection Of Gastric Gistmentioning
confidence: 99%
“…19 Tunneled EFTR may result in lower peritoneal seeding for higher risk SETs but the presence of tumor ulceration often presents difficulty during submucosal dissection and may result in a separate mucosal defect away from the entrance of the tunnel. Procedural difficulty in EFTR may be variable depending on endoscopist experience, 39 lesion size, 40 and tumor location. Submucosal tumors in the fundus have been associated with greater technical difficulty during endoscopic resection.…”
Section: Development and Progress Of Lecs And Related Proceduresmentioning
confidence: 99%